Uji Aktivitas Antioksidan Ekstrak Daun Salam (Syzygium Polyanthum) Dengan Menggunanakan 1,1-Difenil-2-Pikrilhidrazil - Rahman, Nurdin; Bahriul, Putrawan; Diah, Anang Wahid M. (Jurnal Akademika Kimia, 2014)
Antioxidant activity test of bay leave (Syzygium polyanthum) extract using 1,1-diphenyl-2-picrylhidrazyl (DPPH) has been investigated. The aim of this research is to determine antioxidant strength of bay leave (Syzygium polyanthum) extract. The bay leaves used in this research were young, medium, and old leaves categories. Concentration of DPPH free radical after additional bay leave extracts were determined by UV-Vis spectrophotometry. Variation concentrations of bay leave extracts were 20 ppm, 40 ppm, 60 ppm, and 80 ppm. Vitamin C solution was used as the positive control at the similar concentration, while DPPH solution in ethanol absolute was the negative control. The results showed that IC50 values for young, middle, and old leaves extracts were 37.441 ppm, 14.889 ppm, and 11.001 ppm, whereas vitamin C was 9.898 ppm. Based on these IC50 values, vitamin C is the strongest antioxidant than young, middle, and old bay leave extracts, and these extracts are classified as very strong natural antioxidant.